To what extent does riparian culture support eco-culture tourism around the Sungai Kakap market, Kubu Raya district - Equanti, Dian (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The area around Sungai Kakap Market is a traditional market on the banks of the Kakap River which is popular as a tourist destination. With the river as the main tourism attraction, this research aims to identify the riparian culture of the local community; identify eco-cultural tourism aspects; and how the riparian culture supports eco-culture tourism around Sungai Kakap Market. The research uses a qualitative descriptive method with data collection through observation and in-depth interviews. The research results show that riparian culture is visible in the use of rivers for subsistence needs and socio-economic activities; the dimension of eco-culture tourism in the area around Sungai Kakap Market can be seen in community participation in driving river tourism; Riparian culture has not provided positive support for eco-culture tourism because there is no system for managing negative impacts on the environment from community activities.